2014
DOI: 10.1186/1472-6882-14-276
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on patient expectations of treatment outcomes: results from qualitative interviews with patients seeking complementary and alternative medicine treatments for chronic low back pain

Abstract: BackgroundPositive patient expectations are often believed to be associated with greater benefits from complementary and alternative medicine (CAM) treatments. However, clinical studies of CAM treatments for chronic pain have not consistently supported this assumption, possibly because of differences in definitions and measures of expectations. The goal of this qualitative paper is to provide new perspectives on the outcome expectations of patients prior to receiving CAM therapies for chronic low back pain.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 32 publications
(38 reference statements)
2
37
0
1
Order By: Relevance
“…The qualitative studies (Table ) also showed great discrepancy between the desired and the expected outcome: Patients often expressed a want or a need for pain relief or pain cure but predicted substantial less pain relief or no pain reduction at all …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative studies (Table ) also showed great discrepancy between the desired and the expected outcome: Patients often expressed a want or a need for pain relief or pain cure but predicted substantial less pain relief or no pain reduction at all …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found that qualitative findings provided more information about expectations regarding process and structure of care. However, some qualitative studies also restricted themselves to asking focused questions and explored or reported outcome expectations only …”
Section: Discussionmentioning
confidence: 99%
“…Questions were drafted to capture hopes and expectations for CAM treatment effects on three domains identified in previous work 9,10 (pain relief, improved function, and improved mood and overall well-being). Questions were drafted about specific domains (sleep, mood) and how much change individuals hoped for and realistically expected in their back pain, and the impact of back pain on their life in one year.…”
Section: Questionnaire Development: Overviewmentioning
confidence: 99%
“…[9][10][11] Hopes reflect individuals' views of the best-case scenario, whereas expectations are their appraisals of the most likely outcomes, and asking about hope may affect how respondents interpret questions about expectations. [9][10][11] To address these gaps in the literature, a measure of expectations for different CAM treatments for chronic low back pain (CLBP) was developed and evaluated. In recognition of the frequent need in research studies to minimize respondent burden, a short form of this questionnaire was also developed.…”
Section: Introductionmentioning
confidence: 99%
“…De plus, les patients ont compris la nécessité d'une gestion au long cours de leur pathologie ainsi que des notions comme la qualité de vie, de bien-être. D'autres travaux vont dans ce sens, c'est-à-dire une meilleure acceptation par les patients de leur pathologie chronique, une amélioration des stratégies d'adaptation à leur situation et un renforcement de leur implication dans les soins, dans leur santé, notamment pour l'acupuncture [20][21][22]. De la même façon, si l'hypnose et la méditation, classées dans les approches psychocorporelles des médecines complémentaires, montrent une certaine efficacité sur le symptôme évalué directement par des études, néanmoins de qualité variable et assez hétérogènes [23][24][25][26][27], leurs actions sur les aspects cognitifs et affectifs de la douleur paraissent supérieures [28].…”
Section: Quelles Sont Ces Médecines Complémentaires ?unclassified